Pediatric Thrombectomy: Design and Workflow Lessons from Two Experienced Centers - Lauzier, David C. (Stroke, 2021)
Endovascular thrombectomy (EVT) has played a major role in advancing adult stroke care and may serve a similar role in pediatric stroke care. However, there is a need to develop better evidence and infrastructure for pediatric stroke care. In this work, we review two experienced pediatric EVT programs and examine key design features in both care environments, including a formalized protocol and workflow, integration with an adult EVT workflow, simplification and automation of workflow steps, pediatric adaptations of stroke imaging, advocacy of pediatric stroke care, and collaboration between providers, among others. These essential features transcend any single hospital environment and may provide an important foundation for other pediatric centers that aim to enhance the care of children with stroke.